Impact of covid-19 on household food security of red rice farmers dry land in gunungkidul regency - Novri Nur Hasanah Eka (EDP Sciences, 2021)
Red rice is a staple food and is known as germplasm in Gunungkidul Regency. Panggang District is one of the sub-districts that has low productivity in red rice farming. This study aims to determine the contribution of income, food security, and household welfare levels of dry land red rice farmers before Covid-19 and during Covid-19. This research was conducted in Panggang District which was determined purposively. The number of samples taken using the Slovin formula and obtained 100 respondents for sampling using simple random sampling. The data were analyzed using quantitative analysis in the form of farmer household income analysis, contribution analysis, food security analysis, and welfare analysis. The results showed that there was an impact during Covid-19 on the contribution of farmers' income which decreased. The level of food security of farmer households also has an impact, during Covid-19 the number of households in the food insecure category has increased. The level of welfare of farmer households measured using two indicators, namely the Purchasing Power of Farmers' Households and the Income Exchange Rate of the Perani Household showed the same results, namely the impact during Covid-19 was seen by the increase in households with the category of not being prosperous.